Enhancing Human Resource Management Competencies of Preschool Education Institution Directors in The Context of Digital Transformation (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This scientific article is dedicated to a comprehensive study of the human resource management competencies of preschool education institution directors. The article analyzes modern management methods, strategies for developing leadership skills in the context of digital transformation, mechanisms for motivating pedagogical staff, and ensuring their professional development. The study takes into account the newly introduced requirements under the “Resolution No. 531 of the Cabinet of Ministers of the Republic of Uzbekistan, dated August 27, 2024”, as well as opportunities provided within the framework of the Enhanced Partnership and Cooperation Agreement signed with the European Union.